Analysis of Factors Affecting the Intention to Use NFC-Based Payment System - Cindy, Vira Deyana; Widyastuti, Umi; Noviarini, Diena (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2025)
This study aims to examine the influence of Prior Experience on Perceived Ease of Use and Perceived Usefulness, as well as the effects of both perception variables on Intention to Use QRIS Tap. A quantitative approach was employed, with the population consisting of NFC payment users in the Greater Jakarta area. The sample was selected using a purposive sampling method, involving 165 qualified respondents. Data were collected through an online questionnaire using a 6-point Likert scale, and analyzed using SmartPLS and Microsoft Excel. The results reveal that Prior Experience has a significant positive effect on both Perceived Ease of Use and Perceived Usefulness. Furthermore, these two perception variables significantly and positively influence the Intention to Use QRIS Tap. Based on these findings, all four proposed hypotheses in this study are supported.